MODERASI APPROVAL MOTIVATION PADA HUBUNGAN ANTARA SELF-ESTEEM DAN KELELAHAN MENTAL REMAJA AKHIR HINGGA DEWASA AWAL - Zakaria, Nadya Cecilia Esmeralda; Budiarto, Yohanes (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the increasing complaints of mental fatigue among late adolescents to early adults, especially in urban areas that are full of academic, social, and digital pressures. This condition makes internal factors such as self-esteem and social factors such as approval motivation important to review. This study aims to understand the relationship between self-esteem and mental fatigue, as well as to determine whether approval motivation plays a role in influencing this relationship. The study used a quantitative approach with a correlational design. There were 285 participants aged 17 to 28 years. The instruments used included a mental fatigue scale, a self-esteem scale, and an approval motivation scale. All data were obtained through an online survey and analyzed using regression and moderation analysis techniques. The results showed that self-esteem had a negative relationship with mental fatigue, meaning that individuals with higher self-esteem tended to experience lower mental fatigue. Meanwhile, approval motivation was not found to influence the relationship between self-esteem and mental fatigue. These findings confirm that self-assessment plays a greater role in determining the mental condition of late adolescents to early adults than the drive to obtain social approval. In conclusion, strengthening self-esteem is an important aspect in efforts to maintain mental well-being in this age group.